2013
DOI: 10.3389/fncom.2013.00159
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical vector auto-regressive models and their applications to multi-subject effective connectivity

Abstract: Vector auto-regressive (VAR) models typically form the basis for constructing directed graphical models for investigating connectivity in a brain network with brain regions of interest (ROIs) as nodes. There are limitations in the standard VAR models. The number of parameters in the VAR model increases quadratically with the number of ROIs and linearly with the order of the model and thus due to the large number of parameters, the model could pose serious estimation problems. Moreover, when applied to imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 54 publications
1
36
0
Order By: Relevance
“…To our knowledge, there is a dearth of literature describing how activity within a region predicts subsequent activation in the region. A recent study from our group did identify that this intraregional activation prediction is present for LM1, LPMd, SMA, and RPMd (Gorrostieta et al, 2013), largely confirming what we observed in the current analyses. Together the data suggest possible positive feedforward connectivity in these regions.…”
Section: Analysis For the Stroke Studysupporting
confidence: 92%
See 3 more Smart Citations
“…To our knowledge, there is a dearth of literature describing how activity within a region predicts subsequent activation in the region. A recent study from our group did identify that this intraregional activation prediction is present for LM1, LPMd, SMA, and RPMd (Gorrostieta et al, 2013), largely confirming what we observed in the current analyses. Together the data suggest possible positive feedforward connectivity in these regions.…”
Section: Analysis For the Stroke Studysupporting
confidence: 92%
“…Following Gorrostieta et al (2013), the noise u ( s,r ) ( t ) ∈ ℝ P is assumed to follow a Gaussian vector autoregressive model (VAR) with pre-determined order L and condition-dependent VAR coefficients, i.e.,…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vector autoregressive (VAR) modeling of fMRI time series data has been widely used to infer directed connectivity networks of distinct brain regions (Harrison, Penny, & Friston, 2003;Valdés-Sosa, 2004;Deshpande, LaConte, James, Peltier, & Hu, 2009;Valdés-Sosa et al, 2005;Gorrostieta, Ombao, Bedard, & Sanes, 2012;Gorrostieta, Fiecas, Ombao, Burke, & Cramer, 2013;Seghouane & Amari, 2012;Ting, Seghouane, Salleh, & Noor, 2014;Ting, Seghouane, Salleh, & Noor, 2015). Determining the optimal model order p for fMRI data modeling is an important practical as well as a theoretical issue when using VAR models.…”
Section: Introductionmentioning
confidence: 99%